The Metaphysics of Harm. - HANSER, MATTHEW (Philosophy & Phenomenological Research, 2008)
The article discusses on the philosophy on what is it to suffer harm. The author says that harming someone is likely being caused to suffer it which becomes the more fundamental notion. Moreover, accounts of harm are state-based in the sense that to suffer harm is to put into a kind of bad state or condition. Accordingly, the state of badness of the harm defines the harm's status. However, it has been argued that the badness of the event of experiencing harm is in its own right. Several state-based accounts of harm are also discussed including comparative accounts and non-comparative accounts.